Acid induced gelation behavior of skim milk concentrated by membrane filtration. Issue 1 (22nd November 2019) - Li, Ying; Corredig, Milena
Abstract: This work reports a detailed study of the effect of ultrafiltration (UF) and diafiltration (DF) on the acid‐induced gelation behavior of fresh milk retentates (2× and 4×). Concentrates were heated at 80°C for 15 min, and compared to unheated samples. The use of extensive DF caused a significantly greater amount of protein (both caseins and whey proteins) in the supernatant fraction, compared to UF retentates at the same concentration, both in unheated and heated samples. DF retentates showed higher pH of gelation, compared to the corresponding UF retentates. The development of tan δ is reported for the first time as a function of colloidal calcium release, and the protein gelation behavior discussed in light differences in composition of the soluble fraction. The results demonstrate how processing history can affect compositional changes and the gelation behavior of fresh milk retentates. Membrane filtration is a widespread unit operation in the dairy industry, employed either to prepare fresh concentrates for further processing, or ingredients with specific functional properties. This work describes in detail the effect of processing history during membrane filtration on the rheological properties of acid induced gels and will help in optimizing formulations and prepare the right ingredients for the right application. It will also be possible to determine new ways to define processing quality of the milk protein concentrates, as it relates to their ability to form texture in fermented dairy products.